Case report: takotsubo cardiomyopathy after transcatheter aortic valve-in-valve replacement - Steinecker, Matthieu (Eur Heart J Case Rep, 2020)
BACKGROUND : Transcatheter aortic valve implantation (TAVI) has become a first-line therapeutic option in patients with severe, symptomatic aortic stenosis at increased surgical risk. Despite its success, the TAVI procedure has been associated with acute life-threatening complications as myocardial infarction secondary to periprocedural coronary occlusion, annular rupture, or vascular injury. CASE SUMMARY : A 79-year-old woman with a dysfunctional bioprosthetic valve following previous surgical valve replacement was hospitalized in our institution to perform a Valve-in-Valve Transcatheter Aortic Valve Replacement (ViV TAVR). Shortly after the implantation of an Evolut R valve (without complication), left ventricle dysfunction with apical akinesia and basal hyperkinesia was identified during bedside transthoracic echocardiography, in spite of a good prosthesis implantation and function. A concomitant Troponin elevation was noted, and the day-after resting electrocardiogram showed a lateral T-wave inversion. Coronary computed tomography angiography showed no coronary stenosis or occlusion, cardiac magnetic resonance imaging showed no necrosis or fibrosis, and no argument for myocarditis. The patient remained asymptomatic during her hospital stay, and the aforementioned anomalies spontaneously regressed after an in-hospital 2-week surveillance. In the presence of these transient anomalies and after ruling out myocardial infarction and myocarditis, post-procedural stress cardiomyopathy (takotsubo) was diagnosed. DISCUSSION : Post-TAVR stress-related cardiomyopathy seems to be an extremely rare entity. To our knowledge, this is the first case of a takotsubo cardiomyopathy after ViV TAVR. Though the association between the two seems likely to be causal, no clear physiopathological explanation can be formulated.